Occurrence of heatwaves in selected regions of Poland and Greece and the characteristics of their biometeorological conditions - Tomczyk, Arkadiusz M.; Katragkou, Eleni (Quaestiones Geographicae, 2025)
This work aimed to characterise the occurrence of heatwaves and the related bioclimatic conditions in two climate-distinct regions of Europe. This study was based on data of maximum daily air temperature (Tmax), as well as air temperature and humidity at 12:00 UTC, from two meteorological stations in Poznań (Poland) and Thessaloniki (Greece), spanning the summer seasons (the period from May to September) from 1966 to 2022. A hot day was defined as a day with Tmax >90th percentile of the station climatology. Heatwaves were defined as sequences of at least three hot days based on the identified hot days. This study revealed a significant variation in thermal conditions over the examined period in both stations. Both stations showed a statistically significant increase in average Tmax, although changes were more intense in Poznań (0.41°C/10 years). Like Tmax, the 21st-century seasons also stood out in terms of the number of hot days compared to the analysed multi-decade period. This study showed a statistically significant increase in analysed days at both stations, with changes being more intense in Thessaloniki (3.5 days/10 years). The study revealed a significant variation in biometeorological conditions during heatwaves at both stations. Heatwaves in Poznań were characterised by less burdensome conditions compared to those in Thessaloniki.